2011
DOI: 10.1111/j.1475-4991.2010.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Income Poverty and Multidimensional Deprivation: Lessons From Cross‐regional Analysis

Abstract: The study of multidimensional deprivation has become one of the most relevant lines of research in the analysis of low‐income households. The search for significant relationships between multidimensional deprivation and income poverty has been a central issue and most empirical studies have found a very weak link. This paper aims at examining the possibility of an aggregation bias in national‐level studies, which could conceal disparities between regions. As regional differences and decentralization processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 47 publications
5
34
0
4
Order By: Relevance
“…This holds particularly true for measuring child poverty. Indeed, Ayala et al (2011) postulate that the focus on different types of individual wellbeing partly explains the lack of a statistically significant relationship between income poverty and multidimensional poverty.…”
Section: Measurement Errormentioning
confidence: 99%
See 2 more Smart Citations
“…This holds particularly true for measuring child poverty. Indeed, Ayala et al (2011) postulate that the focus on different types of individual wellbeing partly explains the lack of a statistically significant relationship between income poverty and multidimensional poverty.…”
Section: Measurement Errormentioning
confidence: 99%
“…Monetary indicators are considered much more likely to fluctuate in the short term than non-monetary indicators are (Clark and Hulme, 2005;Hulme and Shepherd, 2003) as an increase in monetary resources and may not immediately translate into improvements in non-monetary outcomes (or vice versa). Some consider monetary poverty measures a reflection of a short-term condition, while multidimensional poverty indicators might be more representative of a permanent situation (Ayala et al, 2011) or structural condition of poverty (Battiston et al, 2013).…”
Section: Measurement Errormentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous empirical studies have found a greater correlation between long-term income or consumption and material deprivation, in comparison to current income (Meyer and Sullivan, 2013;Sullivan, Turner and Danziger, 2008;Berthoud, Bryan and Bardasi, 2004;McKay and Collard, 2004). On the other hand, transitions into and out of the labour market and employment insecurity can have a significant effect, independently of income, on the level of material deprivation, reflecting the economic vulnerability associated with the instability of the income flow (Ayala, Jurado and Pérez-Mayo, 2011;Ayllón, Mercader and Ramos, 2007;Layte et al, 2001). Thus, contemporary material deprivation indicators would provide a relatively simple and cost-efficient way to study the outcomes of dynamic processes that otherwise would have to be analysed using longitudinal data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…order to quantify the level of poverty. In this approach, a set of highly empirical contributions summarises information of all the dimensions in a single variable using multivariate statistical methods (Townsend 1979;Desai and Shah 1988; Guio et al 2009;Ayala, et al 2011). …”
Section: Introductionmentioning
confidence: 99%